Effect of various temperature and storage time during process on physical quality and water-holding capacity of broiler breast meats - Suwattitanun, Wilaiwan; Wattanachant, Saowakon (Asia-Pacific Journal of Science and Technology, 2017)
Water holding capacity ofchicken meat is very important for meat quality and meat production yield. Various conditions in product line might affect on quality and water holding capacity of chicken meat. The objective of this study was to determine the effect of process temperature, storage temperature and time and freeze-thaw process on quality ofbroiler breast meat. Higher process temperature inflenced on more lightness (L*), redness (a*), yellowness (b*) and drip loss in breast meat. However, no difference in cooking loss was observed among processing temperature (0-4oC, 8-10oC and 12-15oC for 8 hr). Broiler breast meat chilled at 12-15oCfor72hrhadhigher(P<0.05)inL*, b* and drip loss than thosechilledat 0-4o C. Longerchillingstorage time induced lower L*, a*, shear force value and greater b*, drip and cooking losses. Quality ofbroiler breast meat afterdelay time process at 0-4oC and 12-15oC for 24 h were studied comparatively between freeze-thawed and chilled sample. Freeze-thaw broiler meat had lower (P < 0.05) in L* and a* than those of chilled meat. Freeze-thaw process providedthe greaterdrip loss andlowershearforce in broilerbreastmeat.